Breast cancer screening program for risk groups: facts and perspectives - Carla Andréia Vilanova Marques; Elisabeth Níglio de Figueiredo; Maria Gaby Rivero de Gutiérrez (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to measure the frequency and compliance of breast cancer screening, according to the risk for this disease. Methods: a cross-sectional study with 950 female users of 38 public Primary Health Care services in São Paulo, between October and December 2013. According to UHS criteria, participants were grouped into high risk and standard risk, and frequency, association (p≤0.05), and screening compliance were measured. Results: 6.7% had high risk and 93.3% standard risk, respectively; in these groups, the frequency and compliance of clinical breast examination were 40.3% and 37.1%, and 43.5% and 43.0% (frequency p=0.631, compliance p=0.290). Mammograms were 67.7% and 35.5% for participants at high risk, and 57.4% and 25.4% for those at standard risk (frequency p=0.090, compliance p=0.000). Conclusions: in the groups, attendance and conformity of the clinical breast exam were similar; for mammography, it was higher in those at high risk, with assertiveness lower than the 70% set in UHS.